Interest rate reform and private investment behaviour in developing countries: Evidence from Peru - Uwe Corsepius (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1988)
The principle aims to be achieved by financial liberalization in financially repressed developing countries are to increase the volume of investments and to improve their allocative efficiency. The theoretical and empirical literature stresses the importance of raising real interest rates in countries .with interest rate ceilings and permanently or at least temporary negative real interest rates. This reform proposal is based on the expectation that higher real interest rates would induce private households to save more in the commercial banking system, thereby enabling financial institutions to expand their credit supply to private firms. Assuming that private investments were constrained by the non-availability of credit before the financial reform was implemented, those firms are supposed to increase their real capital formation.
Keywords: 330; Zins; Investition; Peru